Belief System of Wahabi Doctrine in the Kingdom of Saudi Arabia - Yaakop, Rizal; Idris, Asmady (INSANCITA, 2017)
ABSTRACT: One important and most overwhelming issue in Muslim community is the dominance of the Wahabi doctrine in Saudi Arabia, which had been considered as the main religious ideology and the backbone of the Bedouin Arabsâ unification in helping the politico-religious movement led by Sheikh Muhammad ibn Abdel Wahhab and Al-Saud family to form the Kingdom of Saudi Arabia. By using the historical methods and qualitative-descriptive approaches, this paper examines the Wahabi doctrine and its influence; or in more specific way, to define the concept of the Wahabi doctrine, and how far it helped in establishing the Kingdom of Saudi Arabia as well as influencing several Islamic movements in other Muslim territories. The findings show that the Kingdom of Saudi Arabia is generally regarded as one of the earliest initiators of the Islamic reformation from as early as the 18th and 19th centuries, through the âWahabiyahâ movement. Besides that, the Wahabi doctrine also created several Islamic legal decisions or âfatwaâ that for a few Muslim countries are not content with, such as rejecting a âfatwaâ by most of the Sunni scholars that the Prophet Muhammad, after he died, can still intercede or âtawassulâ with his God; rebuffing all âijmaâ or consensus of the religious scholars after the death of the companions of the Prophet Muhammad; declaring other Muslim communities who do not accept the Wahabi doctrine to be infidel; and launching war against all innovations or âbidâahâ in Islam, being anti-modernization, and others.KEY WORD: Wahabi Doctrine; Politico-Religious Movement; Kingdom of Saudi Arabia; Sheikh Muhammad ibn Abdel Wahhab; Al-Saud Family.Â ABSTRAKSI: âSistem Keyakinan Doktrin Wahabi di Kerajaan Arab Saudiâ. Satu isu penting dan paling memberangsangkan dalam komuniti Islam adalah dominasi doktrin Wahabi di Arab Saudi, yang dianggap sebagai ideologi keagamaan utama dan tulang belakang penyatuan orang Badui Arab dalam membantu pergerakan politik-agama yang diketuai oleh Sheikh Muhammad ibn Abdel Wahhab dan keluarga Al-Saud dalam membentuk Kerajaan Arab Saudi. Dengan menggunakan kaedah sejarah dan pendekatan kualitatif-deskriptif, makalah ini mengkaji doktrin Wahabi dan pengaruhnya; atau dengan cara yang lebih spesifik, untuk mendefinisikan konsep doktrin Wahabi, dan sejauh mana ia membantu dalam mewujudkan kerajaan Arab Saudi serta mempengaruhi beberapa gerakan Islam di wilayah-wilayah Islam yang lain. Dapatan menunjukan bahawa Kerajaan Arab Saudi pada umumnya dianggap sebagai salah satu pemula awal reformasi Islam sejak awal abad ke-18 dan ke-19, melalui pergerakan "Wahabiyah". Selain itu, doktrin Wahabi juga membuat beberapa âfatwaâ (keputusan undang-undang Islam) bagi sesetengah negara Islam yang tidak puas hati, seperti menolak âfatwaâ oleh kebanyakan ulama Sunni bahawa Nabi Muhammad, setelah Baginda meninggal dunia, masih dapat memberi syafaat atau "tawassul" dengan Allahnya; menolak semua âijmaâ (konsensus ulama-ulama agama Islam) setelah kematian para Sahabat Nabi Muhammad; mengumumkan masyarakat Muslim lain yang tidak menerima doktrin Wahabi sebagai kafir; serta melancarkan perang terhadap semua âbidahâ (inovasi dalam Islam), sebagai anti-pemodenan, dan lain-lain.KATA KUNCI: Doktrin Wahabi; Gerakan Politik-Keagamaan; Kerajaan Arab Saudi; Sheikh Muhammad ibn Abdel Wahhab; Keluarga Al-Saud.Â Â About the Authors: Assoc. Prof. Dr. Rizal Yaakop is a Lecturer at the Faculty of Social Sciences and Humanities UKM (National University of Malaysia), 43650 Bangi, Selangor Darul Ehsan, Malaysia. Assoc. Prof. Dr. Asmady Idris is a Lecturer at the Faculty of Social Sciences and Humanities UMS (Malaysia University of Sabah) in Kota Kinabalu, Sabah, Malaysia. For academic interests, the authors are able to be contacted via e-mail address at: rizaly@ukm.mySuggested Citation: Yaakop, Rizal & Asmady Idris. (2017). âBelief System of Wahabi Doctrine in the Kingdom of Saudi Arabiaâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Volume 2(2), August, pp.123-136. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 2443-1776. Article Timeline: Accepted (October 28, 2016); Revised (January 20, 2017); and Published (August 30, 2017).